All-in-One Spinal Cord Stimulation in Lymphoproliferative Diseases - Sica, Antonello; Casale, Beniamino; Sagnelli, Caterina; Di Dato, Maria Teresa; Buonavolontà, Pietro; Salzano, Anna Maria; Sagnelli, Evangelista; Famiglietti, Vincenzo; Saracco, Elisabetta; Tammaro, Dario; Papa, Alfonso (Frontiers in Neurology, 2020)
Even patients with lymphoproliferative diseases may develop a persistent chronic pain not responsive to usual treatments due to changes in antibody production and to some treatments like radiotherapy, chemotherapy and the administration of monoclonal antibodies, which further impair the immune defense and induce chronic inflammatory phenomena acting as a substrate for a persistent chronic pain. Five patients with indolent lymphoproliferative diseases were treated for severe pain nonresponsive to other pain-reliever treatments with SCS applied with an All in One Shot (OS) procedure. For all patients the estimated survival time was of 5 years or more. All patients showed a significant reduction of the intensity of pain: the mean Numerical Rating Scale was 7.4 before treatment and 2.2 after. No patient developed adverse events. Supported by the data of this study, we believe extremely reductive and frustrating the habit to deprive patients with an indolent form of lymphoproliferative diseases of the possibility to reduce the intensity of chronic pain by SCS treatment.